Genetic Study of Cerebral Small Vessel Disease in Chinese Han Population - Wang, Yunchao; Shi, Changhe; Li, Yusheng; Yu, Wenkai; Wei, Sen; Fan, Yu; Mao, Chengyuan; Yang, Zhihua; Yu, Lulu; Zhao, Zichen; Li, Shanshan; Gao, Yuan; et al. (Frontiers in Neurology, 2022)
Cerebral small vessel disease is a syndrome of clinical, neuroimaging, and neuropathological manifestations caused by disorders that affect small cerebral vessels. Although the pathogenesis of disease remains unclear, some studies have demonstrated that genetic variants contribute to the development of CSVD. Our study aimed to explore the genetic characteristics of CSVD in the Chinese Han population. We enrolled 188 sporadic CSVD Chinese Han patients whose magnetic resonance imaging results showed grade 2-3 white matter lesions. Whole-exon sequencing of seven monogenic CSVD-related genes, including NOTCH3, HTRA1, COL4A1, COL4A2, GLA, TREX1, and CTSA, was performed, and we identified pathogenic mutations by screening the sequencing results and functional predictive analysis. All mutations were predicted to be pathogenic by the SIFT Score, Polymorphism Phenotyping-2 score, Mutation Taster, Splice site score calculation and MaxEntScan. All mutations were validated in 300 healthy controls. In total, eight mutations were identified in patients with CSVD, including five novel mutations, p.R592C (NOTCH3), p.R1262C (NOTCH3), p.R403W (HTRA1), and c.1274+1G> A (HTRA1), p.G646A (COL4A1) and three reported mutations. None of these mutations were present in 300 healthy controls. No pathogenic mutations in COL4A2, GLA, TREX1 and CTSA were detected. This study identified five novel mutations in CSVD-related genes in Chinese Han patients with sporadic CSVD. Our results expand the genetic profile of CSVD.